The Socio-Political Ideas of BR Ambedkar : Liberal Constitutionalism in a Creative Mould. - Chakrabarty, Bidyut (Milton : Routledge, 2018)
Dr. Bhimrao Ramji Ambedkar (1891-1956), popularly known as Babasaheb stands out for his relentless battle against caste discrimination. He was a voice for the marginalized of India's demography that remained peripheral due to well-entrenched socio-economic and political prejudices.This book is an analytical account of how Ambedkar's socio-political ideas evolved as part of his wider politico-ideological challenge against self-motivated designs for exploitation of human beings by human beings. The author contends that it was an ideological discourse that he built in a context when dominant nationalist viewpoints seem to have hardly left space for any other discourse to grow. The book argues that Ambedkar's socio-political ideas were an outcome of his personal experiences of social atrocities which were justified as integral to the caste system. The book comprises six substantial chapters which delve into the socio-political ideas of BR Ambedkar, concentrating on those sets of ideas through which he established his claim as an original thinker in opposition to the dominant nationalist discourse. Unlike the most conventional studies of Ambedkar's thoughts and ideas, the book provides a new methodological tool to decipher their conceptual roots. It is therefore argued that Babasaheb's unique conceptualization of social justice was not just an outcome of his existential existence of being a Dalit, but an offshoot of his own understanding of liberalism as a mode of emancipating human beings from shackles of authority, power and domination.Examining Ambedkar's ideas, the book charts and examines the growth and consolidation of constitutional democracy in India since it was inaugurated with the acceptance of the 1950 Constitution. It will be of interest to scholars in the fields of Indian political theory, South Asian politics and history.
The British initiatives and gender justiceDecoding the 1951 Hindu Code Bill; Constitutionalizing gender parity; Historical antecedents; Reviewing the argument; Babasaheb's distinct design for gender parity; Concluding observations; Notes; Conclusion; Notes; Select bibliography; Bibliographical note; Select bibliography; Unpublished PhD dissertation; Index.
OCLC-licensed vendor bibliographic record.
Keywords: Ambedkar, B. R. -- 1891-1956 -- Political and social views